Genetic Variation in the Peroxisome Proliferator Activated Receptor-Gamma Gene Is Associated with Histologically Advanced NAFLD - Gawrieh, Samer; Marion, Miranda C.; Komorowski, Richard; Wallace, James; Charlton, Michael; Kissebah, Ahmed; Langefeld, Carl D.; Olivier, Michael (Digestive diseases and sciences, 2012)
Background The peroxisome proliferator activated receptor-gamma ( PPARG ) is a nuclear receptor that regulates adipocyte differentiation, insulin sensitivity and lipid metabolism, thus, it represents a good candidate gene for non-alcoholic fatty liver disease (NAFLD). Purpose and Method We investigated the association of two PPARG variants (Pro12Ala and C1431T) with NAFLD and its histological features. DNA was extracted from 274 archived, formalin-fixed liver biopsy specimens from 212 patients with NAFLD and 62 controls with normal liver histology. Results Individual SNPs did not show significant association with NAFLD or its histological features. A haplotype comprised of both minor alleles (GT) was less enriched whereas a haplotype comprised of the two major alleles (CC) was more enriched in subjects with NAFLD compared to controls [9.3% vs. 28.1% for GT ( P = 0.001, OR 0.26 (range 0.14–0.48) and 80.4% vs. 64.8% for CC ( P = 0.037, OR 2.23 (range 1.30–3.81)]. Both haplotypes were significantly associated with steatosis and fibrosis. The GT haplotype was also associated with lobular inflammation. Conclusions Genetic variation in PPARG is associated with NAFLD, and the GT haplotype is associated with inflammatory and fibrotic changes that denote histologically advanced NAFLD.